2021
DOI: 10.1007/jhep03(2021)209
|View full text |Cite
|
Sign up to set email alerts
|

Single extra dimension from κ-Poincaré and gauge invariance

Abstract: We show that κ-Poincaré invariant gauge theories on κ-Minkowski space with physically acceptable commutative (low energy) limit must be 5-d. The gauge invariance requirement of the action fixes the dimension of the κ-Minkowski space to d = 5 and selects the unique twisted differential calculus with which the construction can be achieved. We characterize a BRST symmetry related to the 5-d noncommutative gauge invariance though the definition of a nilpotent operation, which is used to construct a gauge-fixed act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 59 publications
(156 reference statements)
0
31
0
Order By: Relevance
“…Two interesting value for (ρ c ) is that, if we choose the size of the extra dimension of the order of millimeters, the quanta of mass becomes of the order of the electron mass and by the Fermi order for ρ c we obtained a larger quanta for the mass, say 10 −19 kg or TeV scale. Where the last one recently show to concluded from compact extra dimension by Poincaré symmetry considerations [22]. Therefore it is shown that extra 2d window incorporate to the Dirac magnetic monopole assumption can be resulted to the negative gravity and mass quantization.…”
Section: Quantization Of 3d Particle With 2d Windowmentioning
confidence: 88%
“…Two interesting value for (ρ c ) is that, if we choose the size of the extra dimension of the order of millimeters, the quanta of mass becomes of the order of the electron mass and by the Fermi order for ρ c we obtained a larger quanta for the mass, say 10 −19 kg or TeV scale. Where the last one recently show to concluded from compact extra dimension by Poincaré symmetry considerations [22]. Therefore it is shown that extra 2d window incorporate to the Dirac magnetic monopole assumption can be resulted to the negative gravity and mass quantization.…”
Section: Quantization Of 3d Particle With 2d Windowmentioning
confidence: 88%
“…For future perspectives on model building, it would also be interesting to see what happens when other nonlocal features such as noncommutative geometry are added to this new nonlocal braneworlds. For instance, in the framework of QFT on κ-Minkowski spacetime, recent investigations [172,173] have shown that the consistency of gauge theories requires that gauge fields propagate in 1 EDS! Note -A preliminary version of this study was published on Zenodo, cf.…”
Section: Discussionmentioning
confidence: 99%
“…• Notice that other choices for the derivations are possible. In particular, one could start from the twisted derivations used in [37], [38] (see also [34]) to construct a κ-Poincaré invariant gauge theory on κ-Minkowski space-time which can be viewed as a noncommutative analog of a Yang-Mills theory. These are given by…”
Section: Lorentzian Spectral Triple For κ-Minkowski Space-time: the D...mentioning
confidence: 99%
“…The derivations ∂ ± (47) act on the algebra. This can be translated as an action of the derivations on the Hilbert space (38) which can be determined from the following action on L 2 (R, ds)…”
Section: Lorentzian Spectral Triple For κ-Minkowski Space-time: the D...mentioning
confidence: 99%
See 1 more Smart Citation